PERBANKAN SYARIAH INDONESIA : KINERJA KEUANGAN, PROSPEK DAN TANTANGAN DALAM MENYONGSONG MEA 2015 - Rory Handriano (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, The purpose of this study was to analyze about financial performance, prospects, and challenges Indonesian Islamic banking in facing the AEC 2015. The method used in this research is the study of literature and observations of Bank Syariah Mandiri, Bank Rakyat Indonesia (BRI Syariah), BNI Syariah, Bank Muamalat Indonesia and Bank IFI. Results of this study that the Islamic Bank is a bank that has a financing system that is different from conventional banks, namely the sale and purchase (murabaha, salam, and Istishna), leasing (Ijara) and profit sharing (Musharaka and mudaraba). Opportunities and challenges shows that the hard efforts of all stakeholders of the Islamic financial industry is needed. Necessary integration steps of practitioners, academics and associations in order to development of more effective and efficient because it can avoid redundancy.